2016
DOI: 10.1371/journal.pone.0148291
|View full text |Cite
|
Sign up to set email alerts
|

Unique β-Glucuronidase Locus in Gut Microbiomes of Crohn’s Disease Patients and Unaffected First-Degree Relatives

Abstract: Crohn’s disease, an incurable chronic inflammatory bowel disease, has been attributed to both genetic predisposition and environmental factors. A dysbiosis of the gut microbiota, observed in numerous patients but also in at least one hundred unaffected first-degree relatives, was proposed to have a causal role. Gut microbiota β-D-glucuronidases (EC 3.2.1.33) hydrolyse β-D-glucuronate from glucuronidated compounds. They include a GUS group, that is homologous to the Escherichia coli GusA, and a BG group, that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 62 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…Hallmark features of the disease also include enhanced epithelial permeability and alterations to the resident microbiota (15,298,374), although whether these are a cause or consequence of the disease is still not certain. Studies showing that asymptomatic relatives of IBD patients also have enhanced epithelial permeability and dis-tinct microbial fingerprints suggest that such alterations may be necessary, but not sufficient, for disease progression (136,142,156,225). Furthermore, changes in the profile of luminal bile acids have also been closely associated with IBD progression.…”
Section: B Bile Acids and Ibdmentioning
confidence: 99%
“…Hallmark features of the disease also include enhanced epithelial permeability and alterations to the resident microbiota (15,298,374), although whether these are a cause or consequence of the disease is still not certain. Studies showing that asymptomatic relatives of IBD patients also have enhanced epithelial permeability and dis-tinct microbial fingerprints suggest that such alterations may be necessary, but not sufficient, for disease progression (136,142,156,225). Furthermore, changes in the profile of luminal bile acids have also been closely associated with IBD progression.…”
Section: B Bile Acids and Ibdmentioning
confidence: 99%
“…There are thousands of species present in the gut, and the numerous hydrolases encoded by these species are very important for metabolic homeostasis. β-Glucuronidase is a hydrolase that targets the glucuronidated compounds, releasing glucuronic acid [33] . As our previous study indicated, large amounts of BRB and BRBG could be detected in bile after BRB oral administration, but BRBG could be barely detected in feces (unpublished data).…”
Section: Hydrolyzation Of Brbg In Gut Floramentioning
confidence: 99%
“…Intestinal microbes utilize glucuronides as a carbon source; free GlcA can be metabolized via the Entner–Doudoroff pathway to generate pyruvate that enters the citric acid cycle . While bacterial GUS enzymes have been linked to the GI toxicity of chemotherapeutics and NSAIDs (Figure a), , they may also be involved in carcinogenesis, inflammatory bowel diseases, and gall stone formation. Thus, inhibiting microbial GUS enzymes may improve the tolerance and efficacy of current drugs, while also enabling the treatment or prevention of human disease.…”
Section: Introductionmentioning
confidence: 99%